Comparing the effects of alpha-tocopherol and tocotrienol isomers on osteoblasts hFOB 1.19 cultured on bovine bone scaffold - Nur Farhana Mohd Fozi; James Jam Jolly; Chua, Kien Hui; Ekram Alias; Chin, Kok Yong; Ima Nirwana Soelaiman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Tocotrienol mixtures have been shown to exert anabolic actions on the skeletal system in animal studies, but it is unclear which tocotrienol isomer shows the most prominent effects. This study aims to investigate the most active tocotrienol isomers using hFOB 1.19 human osteoblasts cultured on a bovine bone scaffold. The bovine trabecular bone was sectioned, demineralised and freeze-dried to form the scaffold. hFOB 1.19 osteoblasts were cultured on the bone scaffolds in humidified condition at 37 °C and 5% carbon dioxide with vitamin E isomers (alpha-, beta-, gamma-, delta-tocotrienol and alpha-tocopherol). The cell differentiation capacity of tocotrienol isomers was investigated through morphological observation, alkaline phosphatase (ALP) activity and osteocalcin expression. Changes in the bone scaffolds were determined using histomorphometry methods. Osteoblast culture treated with gamma- and delta-tocotrienols showed a significant increase in ALP activity and osteocalcin expression. Bone structural histomorphometry analysis showed that bone scaffolds treated with gamma- and delta-tocotrienol showed significant increases in bone volume and trabecular thickness. In conclusion, gamma- and delta-tocotrienol show the most prominent bone anabolic effects by increasing osteoblast differentiation and enhancing bone microstructure.